AN UNCOMMON CASE OF FILUM TERMINALE HEMANGIOBLASTOMA NON-ASSOCIATED WITH VON HIPPEL - LINDAU DISEASE - Todor Shamov; Tihomir Eftimov; Georgi K. Georgiev; Rosen T. Rousseff (Peytchinski Publishing, 2023)
A 55-year-old man presented with low backache, paraesthesia, and spasticity of both lower limbs. He had urinary retention and constipation. Investigations revealed a vascular intradural cauda equina tumor. MRI scan demonstrated an enhancing mass at the third and fourth lumbar vertebral levels. There were multiple dilated and tortuous veins draining from both poles of the tumor. At surgery, we found a well-defined tumor with an orange hue and fleshy consistency was encountered arising from the filum terminale, comprising a few adjacent nerve roots. The tumor was excised en bloc. The filum terminale was also been resected. A sporadic hemangioblastoma arising from the filum terminale should be considered as a rare cause of back pain and sciatica. Total excision of the tumor offers a cure.